Effectiveness of prevention of SARS-CoV-2 transmission among unvaccinated Italian healthcare workers - Collatuzzo, Giulia; Mansour, Ihab; Ciocan, Catalina; Ditano, Giorgia; Godono, Alessandro; Rossello, Paola; Coggiola, Maurizio; Pira, Enrico; Boffetta, Paolo; Working Group on Sars-Cov-2 prevention (La Medicina del Lavoro, 2022)
Background: We aimed to investigate the association between personal protective equipment (PPE) use and SARS-CoV-2 infection among healthcare workers (HCWs). Methods: We analyzed occupational surveillance contact forms followed by a PCR test notified between March and September 2020 by Italian HCWs. The odds ratios (ORs) and 95% Confidence Intervals (CIs) for positive PCR based on HCWs and contacts characteristics were calculated through multivariable logistic regression models. When multiple contacts were potentially effective for a PCR test, they were weighted by the inverse of their number. Results: Overall, 4,883 contacts reported by 2,952 HCWs were analyzed, and 224 contacts among 144 HCWs had positive PCR. No difference was found according to sex, age, employment, or job title, except for an OR of 0.30 (95%CI 0.11-0.78) for resident physicians, compared to administrative staff. The ORs for use of surgical mask were 0.59 (95%CI=0.40-0.86) for use only by HCW, 0.49 (95%CI=0.22-1.07) only by the infected person, and 0.40 (95%CI=0.27-0.60) by both, compared to use by neither. Use of other PPEs was not associated with infection, while the OR for hand sanitation was 0.61 (95%CI=0.40-0.93). HCWs reporting fever, cough, and asthenia had a higher risk of infection. Conclusions: Use of surgical masks was associated with a 40-60% lower risk of infection, especially when both HCWs and infected individuals used them. Our results quantify the role played by mask use and hand sanitation in preventing SARS-CoV-2 transmission in high-risk circumstances.